A Novel Approach utilizing Permutation Polynomials over integer rings as a Cryptological Application for Effective Encryption of Digital Images - Balu Wagh, Neha; Kolhekar, Megha (International Journal of Computer Sciences and Engineering, 2025)
Internet Technology and its constant evolvement gives humans an opportunity to be an active explorer over social media and micro blogging sites. Due to which people have resorted to a route of Internet with images, a tempting platform which is hard avoid. This theme gained an overwhelming response as a communication medium for the obvious reason that people nowadays like to share or express their thoughts through images. Unlike text, images helps to annotate viewers' flow of emotions much conveniently with depth. But people relying more on power imagery to share information over unreliable channel, well-known as Internet invites exploitation and misapplication of confidential data which should be avoided. Considering the importance of the issue raised in the light of protecting images, encryption is a way to assure security. Image encryption techniques converts an original image to illegible form, so only authorized access is possible with a key. Over years, different image encryption schemes had been put forward with various issues being addressed according to the requirement of applications. In this paper, we proposed a novel image encryption algorithm based on permutation polynomials over integer rings which makes an attempt to overcome the limitations of existing methods. Here, the original image is scrambled by applying permutation polynomial to its rows and columns. Eventually, the experimental results and calculating the evaluation parameters using MATLAB shows that the proposed encryption scheme achieve satisfactory hiding aspect. Also, the comparison with respect to existing ones is made to analyze performance of the proposed technique.